Designing of optimal warehouse layout and storage location assignment : A case study of an import-export frozen butcher warehouse - Suthipongkeat, Apitchaya; Pongsathornwiwat, Akkaranan; Intalar, Nuchjarin (Journal of Applied Statistics and Information Technology, 2023)
This research aims at designing and determining the optimal warehouse layout and storage location for an import-export frozen butcher warehouse. With on-field problem investigation, the case has an inefficient layout resulting pickers’ unproductive traveling distances. To make an improvement, this research used data of picking frequencies for three months with 5,723 orders in order to sort the picking frequency from high to low and used it for considering appropriate storage location. Three main models of warehouse layouts have proposed: 1) Class-based layout with diagonal and within aisle, 2) Linear Programming model, and 3) Class-based-within Forward Area (FA) model. With performance evaluation of three models with simulation analysis, the results reveal that the class-based-within forward area analysis with combined selective items, so-called Forward SKUs performs the best performance with the highest travel distance reduction. The finding indicates that the best model can decrease the total travel distance from 95,102 to 74,131 meters, accounting for 22.05%.